Prescription opioid use in Israel - the tide has risen, but it's not a tidal wave - Yehuda Neumark; Paola Rosca (BMC, 2024)
Abstract The devastating human and financial costs of the ongoing global opioid crisis underscore the need for comprehensive public health strategies, effective treatment programs, and robust policy interventions to mitigate its impact. Regarding Israel, numerous reports highlight a steady increase since 2000 in prescription opioid use and the shift to more potent opioids particularly fentanyl, particularly among more marginalized population groups. In response to growing concern in the country about the rise in prescription opioid use and the consequential risk of opioid use disorder, the Israeli government, together with the country's health service providers, implemented a series of measures to monitor and regulate opioid prescriptions and balance the need for effective pain management with the prevention of opioid abuse and its associated harms. A national opioid data monitoring system is being established, alongside the provision of addiction training for health professionals, the integration of treatment services for opioid use disorder into the nationalized primary healthcare system, and the expansion of harm reduction strategies to mitigate the health risks associated with opioid use. Additional funding for opioid-related research, and for the broader fields of addictions and mental health, is vital. In conclusion, the sum of the evidence suggests that Israel is not facing an "opioid crisis" Continued commitment, resources, and innovative approaches will be crucial to ensure that the rising tide of opioid use in Israel, particularly during and in the aftermath of the ongoing war, will not become a tidal wave.